Integrated Marketing Communication And Member Engagement In Islamic Microfinance: The Case Of Tabah Product At BMT NU Saronggi - Supriyadi, Supriyadi; Almawadah, Arini (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the implementation of integrated marketing communication strategies on TABAH savings products at BMT NU Saronggi Branch, opportunities and obstacles in its implementation as a strategy to strengthen Islamic microfinance at the community level. This study is a qualitative descriptive case study. This case study was conducted on several staff/employees at BMT NU Saronggi Branch. The results of the study indicate that the implementation of integrated marketing communication strategies on products at BMT NU Saronggi Branch has a significant influence in increasing customer loyalty. This finding, of course, BMT NU Saronggi Branch as a sharia microfinance institution has contributed to increasing sharia financial inclusion in the community. BMT NU is here to provide various forms of services and access to finance for the community according to their needs, one of which is TABAH savings. However, although the number of customers has increased, the communication strategy used has not been fully integrated, so an in-depth study is needed regarding the implementation of IMC.